Staphylococcus lugdunensis: novel organism causing cochlear implant infection - Samina Bhumbra; Mona Mahboubi; R. Alexander Blackwood (MDPI AG, 2014)
A majority of cochlear implant infections are caused by Staphylococcus aureus or Pseudomonas aeruginosa. Reported here is a pediatric patient with a cochlear implant infection caused by methicillin-resistant Staphylococcus lugdunensis, a coagulase-negative Staphylococcus that has only recently been determined to be clinically relevant (1988). Unlike other coagulase-negative Staphylococcus, it is more aggressive, carrying a greater potential for tissue destruction. In pediatrics, the organism is uncommon, poorly described, and generally pan-susceptible. Described herein is the presentation and management of this unusual organism in a pediatric setting.